Expression of Adiponectin and Its Receptors Is Altered in Epithelial Ovarian Tumors and Ascites-Derived Ovarian Cancer Cell Lines. Issue 3 (1st March 2015) - Tiwari, Anupama; Ocon-Grove, Olga M.; Hadley, Jill A.; Giles, James R.; Johnson, Patricia A.; Ramachandran, Ramesh
Abstract : Objectives: Recent evidence suggests that higher body mass index is associated with a modest increase in ovarian cancer risk. Reduced serum levels of adiponectin are correlated with obesity and increased cancer risk. The objectives of the present study are to determine if expressions of adiponectin and its receptors, AdipoR1 and AdipoR2, are altered in epithelial ovarian tumors and ascites-derived ovarian cancer cell lines and to determine if plasma adiponectin levels are altered in the chicken model of ovarian cancer. Methods: Adiponectin, AdipoR1, and AdipoR2 mRNA concentrations in ovaries and chicken ovarian cancer (COVCAR) cell lines were determined by quantitative real-time polymerase chain reaction analysis. Existence of adiponectin isoforms in the ovaries and COVCAR cells was identified by nondenaturing gel electrophoresis. Adiponectin, AdipoR1, and AdipoR2 protein amounts were determined by Western blot analysis. Plasma total adiponectin levels were determined by an enzyme immunoassay. Results: Adiponectin, AdipoR1, and AdipoR2 mRNA concentrations were significantly lower in cancerous ovaries and COVCAR cell lines compared with normal ovaries and normal ovarian surface epithelial (NOSE) cells, respectively. Adiponectin in ovary and COVCAR cell lines appeared as a heavy-molecular-weight isoform that is greater than 720-kd mass. In addition, a lower-molecular-weight adiponectin isoform was found in COVCAR cells but not in NOSE cells. Adiponectin and AdipoR1 protein concentrations were not different in COVCAR cell lines compared with NOSE cells. However, AdipoR2 protein concentrations were significantly higher in cancerous ovaries but lower in COVCAR cell lines compared with normal ovaries and NOSE cells, respectively. Plasma adiponectin concentrations were not different in chickens that had ovarian carcinoma compared with control animals. Conclusions: Expression of adiponectin in ovarian tumors and in metastatic ovarian tumor cells is likely to affect cellular metabolism and proliferation through activating AdipoR1 and/or AdipoR2. Plasma adiponectin levels may not be predictive of advanced stages of ovarian tumor in the chicken model.